The Impact of a Training Program Using Machines and Free Weights on Developing Maximum Muscular Power Among Bodybuilders - Esam Najeh Abu-Shihab; Mahmoud Ali Al-Haliq (Deanship of Scientific Research (DSR), the University of Jordan, 2021)
This study aims at identifying the impact of a training program using machines and free weights on developing the maximum muscular power among bodybuilders. The study sample consisted of twelve bodybuilders, who were divided into two identical groups, with six bodybuilders in each group. The individuals were randomly chosen from Turbo Gym Center for bodybuilding. The study used an experimental approach. The results revealed that there are statistically significant differences at (α≤0.05) between pre- and post-measurements using machines on developing maximum muscular power in favor of the post-measurement among bodybuilders. The results revealed that there are statistically significant differences at (α≤0.05) between pre- and post-measurements using free weights on developing the maximum muscular power in favor of the post measurement among bodybuilders, while the results showed that there are no statistically significant differences at (α≤0.05) in the post measurement between the group of machines and the group of free weights on developing the maximum muscular power in favor of the post measurement among bodybuilders. In light of the results, the researchers recommend the necessity of using two training programs and integrating them as a method to improve maximum muscular power among bodybuilders in Jordan and not depending on a single training method for a long period of time.